On the behaviour of lightning current for the case of striking to tall strature - Izadi, Mahdi; Ab Kadir, Mohd Zainal Abidin (IEEE, 2014)
In this paper, the behaviour of lightning current wave shapes at different heights along a tall tower are studied and the simulated current compared to the corresponding measured current obtained from a real tall structure. Further, the effects of ground reflection and also the tower top reflection factors on the peak values of current and current peak time at different heights along a tower are studied and the results discussed accordingly.